Kebijakan Pendidikan Ramah Bertangan Kidal di Universitas Islam Negeri Sumatera Utara Medan - Mardianto Mardianto; Makmur Syukri; Irwan S (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2021)
The aims objectives of the study are 1) to examine the extent to which the policy of North Sumatra State Islamic University Medan towards left-handedness, 2) to prepare strategic policies in order to fulfill left-handed facilities and infrastructure, and 3) to facilitate left-handed students in conducting lecture activities in the classroom. The research method uses qualitative research methods with a phenomenological approach, which is an approach or search to explore and understand a central phenomenon. This research was conducted on campuses I, II, III and IV UIN North Sumatra Medan. The number of participants in this study were 30 people consisting of 9 lecturers, 3 educators and 18 students. This research was conducted from May – July 2021. Based on the results of the research that has been carried out, 3 important themes were obtained that reflect the condition of the facilities that do not pay attention to left-handed individuals, namely 1) Consideration of left-handed friendly facilities, 2) Campus facilities are not left-handed friendly, and 3) Barriers arising related to facilities that are not left-handed friendly. With this research, the rectorate can use the results of this research as a reference source in making left-handed-friendly planning as early as possible, both in the form of procurement of lecture facilities and when collecting student data based on the website.